Environmentally friendly wollastonic- Based.. - Wan Muhammad Akram Ashmawi Bin Wan Mustaffa (2023)
This thesis refers to the creation of significant dissertation aims which are to assess the valuable impacts of various sintering technique and composition in enhancing the mechanical properties and physical properties of the wollastonite-based composite without affecting its mechanical properties and to create an ageing resistant bio composite. The main range of the study focuses on the compatibility of the composite beased on the mechanical and micro-structural wollastonite basis. In order to check the goals, the information is gathered from few studies, including Density and hardness of Vickers and SEM observation. The potential of this study is rationalized by the ability of wollastonite to replace titanium as a latest medical product in terms of its bio-ceramic characteristics for the bone implant properties. This is due to the high cost of titanium. Few techniques under mechanical and micro-structural characteristics were used to accomplish these projects goals. The compact Wollastonite base composite powder is fully converted into strong mass of wollastonite base composite by a 2-hour density test, hardness test, shrinkage rate, and compressive strength. The SEM monitoring was used to check the grain borders and the loss of pores after sintering. The results show that, after 2 hours of hold time, wollastonite-base composite can completely become solid after sintering above 1230 ° C. Composition No. 3 that is 50 percent Wollastonite/20 percent aluminium Oxide/30 percent Cerium Oxide at 1250 ° C are the finest mechanic and micro structural characteristics.